Corrupción y Arbitraje: A propósito de las Reglas IBA sobre conflictos de intereses - Ezcurra Rivero, Huáscar (Pontificia Universidad Católica del Perú, 2015)
In recent decades the arbitration has undergone extensive development in the Peru. However, this did not mean the absence of corruption in the arbitral proceedings. in this article the author points out some examples in which corruption manifests itself within them. Also, possible solutions are addressed with particular emphasis on competition, and its necessary condition: information. On this last, the iBA rules acquire special relevance for the resolution of conflicts of interest.

En las últimas décadas el arbitraje ha experimentado un amplio desarrollo en el Perú. Sin embargo, esto no significó la ausencia de corrupción en los procesos arbitrales. e n el presente artículo el autor señala algunos ejemplos en los que la corrupción se manifiesta dentro de ellos. Asimismo, se abordan sus posibles soluciones, con especial énfasis en la competencia y su condición necesaria: la información. s obre esta última adquieren especial relevancia las Reglas IBA para la resolución de conflictos de intereses.
Corruption and Arbitration: With regard to the IBA Rules on conflicts of interest
Keywords: Arbitration; Competence; Information; Iba Rules; Arbitraje; Competencia; Información; Reglas Iba; https://purl.org/pe-repo/ocde/ford#5.05.00